Resolution of Uncontrolled Type 2 Diabetes after Laparoscopic Truncal Vagotomy, Subtotal Gastrectomy, and Roux-en-Y Gastrojejunostomy for a Patient with Intractable Gastric Ulcers - Laura F. Tait; Gezzer Ortega; Daniel D. Tran; Terrence M. Fullum (Case Reports in Surgery)
Background. Laparoscopic Roux-en-Y gastric bypass (LRYGB) has been shown to be an effective treatment for type 2 diabetes mellitus (T2DM) in patients with morbid obesity. However, it is unclear just how effective the LRYGB procedure is on T2DM for patients with BMI less than 35 kg/m2. We report one obese patient with T2DM who did not meet the current NIH criteria for morbid obesity surgery. This patient underwent a laparoscopic truncal vagotomy, subtotal gastrectomy, and Roux-en-Y gastrojejunostomy for intractable gastric ulcers and subsequently had full resolution of her T2DM. Methods. A 48-year-old patient with a BMI of 34.6 kg/m2 underwent a laparoscopic truncal vagotomy, subtotal gastrectomy, and Roux-en-Y gastrojejunostomy for intractable gastric ulcers. The patient was seen 3 months preoperatively, followed for 24 months postoperatively, and evaluated for postoperative complications, weight loss, and improvement in comorbidities. Results. The patient had no postoperative surgical complications. Her BMI decreased from 34.6 kg/m2 to 22.3 kg/m2 by 24 months postoperatively. Significant improvements in her fasting blood glucose levels were seen 10 days postoperatively from a preoperative level of 147 mg/dl to 97 mg/dl. Conclusion. Patients with a BMI less than 35 kg/m2 and uncontrolled T2DM may benefit from a laparoscopic Roux-en-Y gastric bypass.